Bassoon controls synaptic vesicle release via regulation of presynaptic phosphorylation and cAMP - Montenegro-Venegas, Carolina; Guhathakurta, Debarpan; Pina-Fernandez, Eneko; Andres-Alonso, Maria; Plattner, Florian; Gundelfinger, Eckart D.; Fejtova, Anna (EMBO Reports, 2022)
Neuronal presynaptic terminals contain hundreds of neurotransmitter-filled synaptic vesicles (SVs). The morphologically uniform SVs differ in their release competence segregating into functional pools that differentially contribute to neurotransmission. The presynaptic scaffold bassoon is required for neurotransmission, but the underlying molecular mechanisms are unknown. We report that glutamatergic synapses lacking bassoon feature decreased SV release competence and increased resting pool of SVs as assessed by imaging of SV release in cultured neurons. CDK5/calcineurin and cAMP/PKA presynaptic signalling are dysregulated, resulting in an aberrant phosphorylation of their downstream effectors synapsin1 and SNAP25, well-known regulators of SV release competence. An acute pharmacological restoration of physiological CDK5 and cAMP/PKA activity fully normalises the SV pools in neurons lacking bassoon. Finally, we demonstrate that CDK5-dependent regulation of PDE4 activity interacts with cAMP/PKA signalling and thereby controls SV release competence. These data reveal that bassoon organises SV pools in glutamatergic synapses via regulation of presynaptic phosphorylation and cAMP homeostasis and indicate a role of CDK5/PDE4/cAMP axis in the control of neurotransmitter release.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Bassoon; neuromodulation; neurotransmission; PDE4; synaptic vesicle recycling